RELATIONSHIP LEVELS OF PARENT'S CAREFULNESS IADVISING CHILDREN WITH SEXUAL BEHAVIOR IN KARYA VILLAGE - Fithri , Nurhamida (International Archives of Medical Sciences and Public Health, 2025)
Adolescence is a developmental phase characterized by physical and psychosocial changes. Social issues arising from adolescent life have persisted for decades, including the concerning and deviant sexual behavior problem. The aforementioned concerns may be mitigated through the adolescent's parent-family relationship, which serves to instill accurate notions regarding appropriate conduct. The purpose of this research is to establish a correlation between the degree of parental guidance regarding adolescent sexual behavior and the level of parental care. The methodology. This is a quantitative study employing a cross-sectional design. This study's sample comprised 38 individuals who satisfied the inclusion and exclusion criteria. Primary data collection methods involved the distribution of questionnaires to participants. In the processing of data, univariate and bivariate analyses were utilized. Findings: The results of this study suggest that parental care is beneficial. The p-value obtained from bivariate analysis using the chi-square test was 0.012. In conclusion, it is suggested that parents maintain positive relationships with their children in order to ensure that they feel secure and at ease within the household, and to enable the children to recognize and understand their roles and responsibilities.